Peningkatan Keterampilan Membaca Pemahaman Peserta Didik menggunakan Model Cooperative Integrated Reading Composition berbantuan Canva di Kelas V SDN 03 Binuang Kecamatan Pauh - Andhina, Jihan Aulia; Desyandri, Desyandri (Asian Journal of Early Childhood and Elementary Education, 2025)
Reading comprehension is a fundamental skill for elementary school students; however, observations in Grade V at SDN 03 Binuang, Pauh District, revealed that this skill remains low, particularly in identifying main ideas, analyzing new vocabulary, and summarizing texts. This study aims to improve reading comprehension skills through the implementation of the Cooperative Integrated Reading and Composition (CIRC) model supported by Canva. The method used was Classroom Action Research (CAR) conducted over two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects included the classroom teacher as observer, the researcher as practitioner, and 28 students. Instruments used included observation sheets, reading skill tests, and documentation. The results showed a significant improvement in reading comprehension skills. In the second cycle, the teaching module received a 100% rating, teacher activity reached 100%, student activity increased to 95%, and the average student reading comprehension score rose from 66.23 in the first cycle to 86.68 in the second. These findings demonstrate that the application of the CIRC model supported by Canva is effective in enhancing the reading comprehension skills of Grade V students at SDN 03 Binuang.